Analysis of the Application of Utmost Good Faith Principles in Personal Accident Insurance Agreements (Case Study of PT Asuransi Askrida Syariah Medan Branch) - Aida Malan Sari; Yenni Samri Juliati Nasution (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Personal accident insurance is protection against all risks suffered by a person resulting in death and accident to someone. One of the principles that is firmly held in insurance is the principle of utmost good faith. This principle means that a person is obliged to provide honest information about what is insured to the insurer and vice versa the insurer must also provide honest information to the insured. This study aims to determine the application of the principle of utmost good faith in the personal accident insurance agreement at PT. Asuransi Askrida Syariah Medan Branch. The method used in this study is a qualitative method by means of interviews and theoretical studies taken from scientific works, books, journals, and other reference materials. The results of this study show that in entering into an agreement, the principle of good faith (Utmost Good Faith) is the basic principle that must be fulfilled by the parties, where the parties must uphold honesty in providing important matters related to the insurance agreement.